Analysis on the causes of unsatisfactory prevention effect of postpartum VTE in Chinese women - Yonghui Xu; Fei Xiao; Ji He; XingSheng Xue; Yangting Li; Sha Zhu (Scientific Reports)
Abstract Preventing venous thromboembolism (VTE) in obstetrics remains challenging, with cases still occurring despite preventive measures. The aim of this study is to investigate the underlying causes by analyzing potential issues in current postpartum VTE prevention strategies in China. This retrospective study was conducted in our hospital from May 2021 to August 2024. VTE risk was assessed using the Chinese Expert Consensus on VTE Prevention and Treatment during Pregnancy and Puerperium (Chinese Consensus), and preventive measures were implemented accordingly. Clinical variables, timing of prophylaxis, and the predictive accuracy of the Chinese Consensus were analyzed. The VTE group had higher D-dimer levels and longer hospital stays and shorter gestational ages (P < 0.05). Significant differences were observed in postpartum hemorrhage (PPH), premature birth, autoimmune diseases, and cesarean delivery (P < 0.05). Despite 65.4% receiving thromboprophylaxis, 25.2% developed VTE, with higher incidences in those without prophylaxis. Pneumatic therapy and LMWH were effective in high-risk patients (P < 0.05). Early VTE occurred 6 h postpartum, with 41.8% within 48 h. Most preventive measures were initiated at 24–48 h postpartum, potentially delaying optimal protection. The ROC analysis showed an AUC of 0.497 (P = 0.937), indicating limited predictive efficacy of the Chinese Consensus. Current postpartum VTE prevention is inadequate, as some at-risk patients still miss the opportunity for pneumatic therapy and LMWH anticoagulation after delivery. Initiating LMWH prophylaxis 24 h postpartum appears to be delayed. The predictive ability of the Chinese Consensus for assessing VTE risk is limited. Future research is essential to optimize prevention strategies and reduce the incidence of postpartum VTE.